X-linked retinoschisis: mutation spectrum and genotype-phenotype relationship in an Italian pediatric cohort. (2nd January 2023) - Fortunato, P.; Pagliazzi, A.; Bargiacchi, S.; Marziali, E.; Sodi, A.; Caputo, R.; Passerini, I.; Pelo, E.; Bacci, G. M.
ABSTRACT: Background: X-linked juvenile retinoschisis (×LRS) is an X-linked vitreoretinal degenerative disease that consists of variable phenotypes ranging from severe early-onset defects to subtle abnormalities diagnosed in elderly patients. XLRS is caused by a loss of function of the protein Retinoschisin (RS1), which is essential to preserve retinal integrity and function of photoreceptor-bipolar synapse. The literature data so far mostly agree on the absence of a clear genotype-phenotype correlation in XLRS. We reviewed clinical and molecular characteristics of a cohort of Italian pediatric XLRS patients to assess the presence of a correlation between genotype and phenotype severity. Materials and methods: We retrospectively examined clinical and genetic features of a cohort of 27 XLRS patients. In this study we included patients with a diagnosis of XLRS confirmed by fundus photography, spectral domain optical coherence tomography, and molecular analysis and with an onset of less than 10 years of age. We sorted RS1 variants according to their effect of RS1 structure and function in three separate groups. Results: According to previous studies, we did not observe a conclusive genotype-phenotype correlation in our cohort; nevertheless, we noticed that patients harboring RS1 variants leading to RS1-secreted mutants show a more homogeneous phenotype, with an overall good visual acuity, compared to the other two groups. Conclusions: Our data support the hypothesis that secretion profile of RS1 could influence the severity of the phenotype. More extensive and functional studies are needed to acquire notions in view of the opportunity of gene replacement therapy for XLRS patients.